Fair Value Accounting, Historical Cost Accounting, and Systemic Risk - Greenberg, Michael D.; Helland, Eric; Clancy, Noreen; Dertouzos, James N. (RAND Corporation, 2023)
In the wake of the 2008 financial crisis, conflicting arguments have been made about fair value accounting (FVA) versus historical cost accounting (HCA) and the role that each played in the crisis. This report examines the relationship between both types of accounting practices and systemic risk in the financial sector, providing recommendations on how FVA and HCA can both be improved.